The Ahmadiyah Community’s Non-Confrontational Advocacy Strategy In Defending Religious Freedom In Banjarmasin - Husna, Nur (AL-ADYAN, 2026)
This study examines the non-confrontational advocacy strategies employed by the Jemaat Ahmadiyah Indonesia (JAI) in maintaining religious freedom in Banjarmasin, South Kalimantan. Ahmadiyah is a religious minority group that frequently encounters social and regulatory pressures, making its efforts to safeguard constitutional rights a significant issue in the discourse on religious freedom in Indonesia. This study aims to analyze the guarantees of freedom of religion or belief experienced by the Ahmadiyya community in Banjarmasin and to identify the forms of advocacy undertaken in response to social, political, and institutional challenges within their living environment. This research employs a qualitative approach using a case study method. Primary data were obtained through in-depth interviews with local leaders of the Jemaat Ahmadiyah Indonesia in Banjarmasin, supported by limited observation and a review of relevant documents. The findings reveal that the advocacy strategies adopted by the JAI community in Banjarmasin tend to be adaptive and non-confrontational. These strategies are manifested through strengthening internal solidarity, religious guidance and mentoring, limited coordination with local community leaders, participation in social activities without open proselytization, and the use of religious literature to preserve community identity. Although the community continues to face stereotypes and social pressures, these strategies have contributed to maintaining the relative continuity and stability of the community’s religious activities in a conducive manner.